2012
DOI: 10.1002/path.3987
|View full text |Cite
|
Sign up to set email alerts
|

Integrated genome and transcriptome sequencing identifies a novel form of hybrid and aggressive prostate cancer

Abstract: Next-generation sequencing is making sequence-based molecular pathology and personalized oncology viable. We selected an individual initially diagnosed with conventional but aggressive prostate adenocarcinoma and sequenced the genome and transcriptome from primary and metastatic tissues collected prior to hormone therapy. The histology-pathology and copy number profiles were remarkably homogeneous, yet it was possible to propose the quadrant of the prostate tumour that likely seeded the metastatic diaspora. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 52 publications
2
70
0
Order By: Relevance
“…For DNA and RNA isolation, patient and xenograft tumor sections were processed as previously described (22). We performed genome copy-number profiling using the Agilent SurePrint G3 Human CGH 4 Â 180K and 8 Â 60K Microarray platforms.…”
Section: Copy Number and Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For DNA and RNA isolation, patient and xenograft tumor sections were processed as previously described (22). We performed genome copy-number profiling using the Agilent SurePrint G3 Human CGH 4 Â 180K and 8 Â 60K Microarray platforms.…”
Section: Copy Number and Gene Expression Analysismentioning
confidence: 99%
“…We performed genome copy-number profiling using the Agilent SurePrint G3 Human CGH 4 Â 180K and 8 Â 60K Microarray platforms. Of note, 0.5 mg of genomic DNA was used for hybridization, according to the manufacturer's standard protocols as previously described (7,22). Limited sample availability of patient samples 972 and 1,005 prevented array comparative genomic hybridization (aCGH) analysis.…”
Section: Copy Number and Gene Expression Analysismentioning
confidence: 99%
“…Different amounts (2,5,8,10, and 12 µg) of α-mouse HRP-IgG were conjugated onto MWCNTs as outlined in our protocol. A diluted (1:10) portion of each sample was loaded onto a microtiter plate and mixed with chemiluminescent solution.…”
Section: Psma Antibody Selection and Nearfield Targeting Of Lncap Cellsmentioning
confidence: 99%
“…CaP studies have shown extensive genetic alterations exemplified by single missense mutations, copy number variation, splicing variants, genetic rearrangements, and short DNA alterations in a large number of genes. 3,[7][8][9][10][11][12] However, physical agent therapies are immune to genetic alterations, as they are more likely to deliver damaging entities to a targeted "area" or "field," and as such are lethal to tumor cells irrespective of their genetic background, as long as they are present within the targeted area.…”
Section: Introductionmentioning
confidence: 99%
“…Genome copy number profiling was performed on Agilent SurePrint G3 Human CGH Microarray Kit, 4 Â 180 K in 4 ENZ-R LNCaP and 2 CRPC LNCaP xenografts tumors as described previously (27). Array CGH copy number data are available at GEO accession number GSE55345.…”
Section: Molecular Profilingmentioning
confidence: 99%